2017
DOI: 10.1111/ddi.12692
|View full text |Cite
|
Sign up to set email alerts
|

Does one size fit all? A multispecies approach to regional landscape corridor planning

Abstract: Aim The practical value of the single‐species approach to conserve biodiversity could be minimal or negligible when sympatric species are limited by factors that are not relevant to the proposed umbrella species. In this study, we quantitatively evaluated as follows: (1) habitat suitability and potential movement corridors of a single umbrella species, giant panda (Ailuropoda melanoleuca); (2) habitat suitability of sympatric mammals; and (3) the potential effectiveness of the single‐species corridor planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 42 publications
5
29
0
Order By: Relevance
“…Our study clearly showed that multitaxa surrogates are best in representing terrestrial vertebrates in conservation areas (Figures 2 and 3) in agreement with other studies (Forest, 2017;Grantham et al, 2010;Leal et al, 2010;Lentini & Wintle, 2015;Lindenmayer et al, 2015;Wang et al, 2018). It is likely that when more taxa are included as surrogates, a higher diversity of habitat types is included resulting in a better representation of all biodiversity features in conservation areas (Grantham et al, 2010;Leal et al, 2010;Wang et al, 2018). This idea is supported by the fact that birds performing best as single-taxon surrogates cover a wider range of habitat types compared to other vertebrates (García-Mendoza et al, 2004), but this hypothesis needs to be tested more rigorously (Margules & Sarkar, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study clearly showed that multitaxa surrogates are best in representing terrestrial vertebrates in conservation areas (Figures 2 and 3) in agreement with other studies (Forest, 2017;Grantham et al, 2010;Leal et al, 2010;Lentini & Wintle, 2015;Lindenmayer et al, 2015;Wang et al, 2018). It is likely that when more taxa are included as surrogates, a higher diversity of habitat types is included resulting in a better representation of all biodiversity features in conservation areas (Grantham et al, 2010;Leal et al, 2010;Wang et al, 2018). This idea is supported by the fact that birds performing best as single-taxon surrogates cover a wider range of habitat types compared to other vertebrates (García-Mendoza et al, 2004), but this hypothesis needs to be tested more rigorously (Margules & Sarkar, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Our study clearly showed that multitaxa surrogates are best in representing terrestrial vertebrates in conservation areas (Figures 2 and 3) in agreement with other studies (Forest, 2017;Grantham et al, 2010;Leal et al, 2010;Lentini & Wintle, 2015;Lindenmayer et al, 2015;Wang et al, 2018). Single-taxon surrogates with a higher number of species such as birds performed better, increasing the representation of other terrestrial vertebrate taxonomic groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, when the survey is robustly designed, the entire population in the area sampled is assumed to be surveyed, including non-collared animals. Although camera trap data is increasingly widespread and available, because it is often easier and cheaper to obtain at a large scale than satellite collar data, their use in estimating functional connectivity has been very scarce (but see [16]).…”
Section: Introductionmentioning
confidence: 99%